Condición y educación Bucodental y otros determinantes de la salud en personas adultas mayores de seis cantones del Área Metropoliana - Murillo-Bolaños, Olga M. (2012)
Given the rapid increase in the aged population of Costa Rica and the lack of new knowledge on the dental conditions of the elderly and other health determinants, a epidemiological study was carried out including 1566 persons older than 60 years in six municipalities of the Greater Metropolitan Area. The general results obtained were: a high 45% rate of edentulous, with a statistically positive difference (p=0,00001) en all municipalities. In women the edentulous rate is more severe, being statistically significant at a 90% confidence level. Elderly people in San Pedro de Montes de Oca were the ones maintaining a high number of their natural dental pieces. A high rate of 43% was found of root caries. The need for prosthesis was found in 55% of cases, together with a bad state of the prosthesis in those that have them, due to prolonged use. The main conclusion was that the aged population had a deteriorated buco-dental condition. A perceived lack of knowledge on buco-dental health among this population, gave origin to a second stage project directed at providing information on different topics related with this issue. In the second stage, 403 persons were involved belonging to the same geographical areas. The method used was based on applying different learning techniques. Such as videos, talks, dramatizations, etc. Two questionnaires were applied, one previous to and another a week after the two educational interventions. Topics included in the events were: eradicating myths on reasons for tooth loss, consequences of sleeping with dentures, and instructions on the correct way of brushing teeth and clearing of prosthesis. Other specific topics covered included: halitosis, exostomy, periodontal disease, nutrition, self-esteem and gastritis. It was found that the participating elderly persons were able to learn at their own speed which points out the need for a continuing (on- going) education on these matters. It was concluded as well, the difficulty of eliminating in this population certain strongly-held myths such as it been natural to loose their teeth in their old age.